In silico docking and ADMET studies on clinical targets for type 2 diabetes correlated to in vitro inhibition of pancreatic alpha-amylase and alpha-glucosidase by rutin, caffeic acid, p-coumaric acid, and vanillin - Apostolides, Zeno (University of Pretoria, 2022)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2021.